The impact of chronic stress on the human body and the role of psychoeducation in reducing its mental manifestations - Shuliakova Марія; Ratsyborynska-Polyakova Наталія (Psychosomatic Medicine and General Practice, 2024)
In wartime, the impact of chronic stress is undeniable. We may not pay attention to it, but our body, brain and hormonal background are undergoing changes. Сhronic stress affects all systems of the body. The long-term activation of the stress response system and the overexposure to cortisol and other stress hormones that come with it can disrupt almost all of your body’s processes. This can put you at increased risk for a variety of physical and mental health problems, including anxiety, depression, digestive issues, headaches, muscle tension and pain, heart disease, heart attack, high blood pressure, stroke, sleep problems, weight gain, and memory and concentration impairment. Some studies have shown that stress has many effects on the human nervous system and can cause structural changes in different parts of the brain [14]. Chronic stress can lead to atrophy of the brain mass and decrease its weight [23]. These structural changes bring about differences in the response to stress, cognition and memory [14]. Of course, the amount and intensity of the changes are different according to the stress level and the duration of stress[14].